УМОВИ ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ САМОСТІЙНОЇ РОБОТИ УЧНІВ (Педагогіка вищої та середньої школи, 2001)
The article deals with material about methods and ways of efficiency improvement of the independent pupils' work at the English language learning, also are examined the practical moments of the lessons' practice.